2003
DOI: 10.1046/j.1440-1746.2003.02962.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the albumin‐γ‐glutamyltransferase isoenzyme as a diagnostic marker of hepatocellular carcinoma‐complicating liver cirrhosis

Abstract: Albumin-gamma-glutamyltransferase appears to be a sensitive diagnostic marker of both advanced and small hepatocellular carcinoma-complicating liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…that circulating lipoproteins are GGT carriers and that GGT is too lipophilic to circulate in a free form [26]. Furthermore, we also observed that plasma f-GGT fraction has a MW corresponding to the free GGT protein, thus demonstrating that part of plasma GGT do not require any carrier, such as lipoproteins [26] or albumin [27], to be transported in blood.…”
Section: Discussionmentioning
confidence: 50%
“…that circulating lipoproteins are GGT carriers and that GGT is too lipophilic to circulate in a free form [26]. Furthermore, we also observed that plasma f-GGT fraction has a MW corresponding to the free GGT protein, thus demonstrating that part of plasma GGT do not require any carrier, such as lipoproteins [26] or albumin [27], to be transported in blood.…”
Section: Discussionmentioning
confidence: 50%
“…A focus on these neglected enzyme groups (isomerases, transferases, and synthetases) should not only extend the spectrum using AuNPsbased enzyme assays, but also inspire the development of AuNPsbased assays for new targets. [136][137][138] Despite the benefits presented by these nano diagnostic systems, there is still a long way to go before the extensive application of colorimetric AuNPs can offer effective diagnostic tests that can be translated into the laboratory or testing near patient setting.…”
Section: Discussionmentioning
confidence: 99%
“…5 Nevertheless, serum AFP is not particularly efficient in detecting HCC at early stages, and its specificity is often shadowed by high false positive signals from patients with other liver-related diseases such as viral hepatitis and cirrhosis. 6 In this regard, several groups have recently suggested several soluble tumor markers such as glypican-3, 7 γ-glutamyltransferase II, 8 des-γ-carboxypro thrombin, 9 lens culinaris agglutinin-reactive AFP 10 and α1-antitrypsin, 11 that may improve the detection rate for early HCC. Nevertheless, their clinical utilities remain to be further determined in multicenter clinical studies.…”
Section: Introductionmentioning
confidence: 99%